2009
DOI: 10.1128/jvi.02285-08
|View full text |Cite
|
Sign up to set email alerts
|

The Receptor Complex Associated with Human T-Cell Lymphotropic Virus Type 3 (HTLV-3) Env-Mediated Binding and Entry Is Distinct from, but Overlaps with, the Receptor Complexes of HTLV-1 and HTLV-2

Abstract: Little is known about the transmission or tropism of the newly discovered human retrovirus, human T-cell lymphotropic virus type 3 (HTLV-3). Here, we examine the entry requirements of HTLV-3 using independently expressed Env proteins. We observed that HTLV-3 surface glycoprotein (SU) binds efficiently to both activated CD4 ؉ and CD8 ؉ T cells. This contrasts with both HTLV-1 SU, which primarily binds to activated CD4 ؉ T cells, and HTLV-2 SU, which primarily binds to activated CD8 ؉ T cells. Binding studies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Unfortunately, serum or plasma was not available from animals Cmo8699AB and Cni7867AB to confirm this hypothesis. The STLV-3d(Cmo8699AB) SU also contains highly conserved residues believed important for viral entry (data not shown) similar to those described recently for HTLV-3b(Pyl43) [ 47 ].…”
Section: Resultssupporting
confidence: 72%
“…Unfortunately, serum or plasma was not available from animals Cmo8699AB and Cni7867AB to confirm this hypothesis. The STLV-3d(Cmo8699AB) SU also contains highly conserved residues believed important for viral entry (data not shown) similar to those described recently for HTLV-3b(Pyl43) [ 47 ].…”
Section: Resultssupporting
confidence: 72%
“…HTLV-3/-4 tropism in vivo is currently unknown, yet it is clear that the virus infects at least cells that belong to PBMCs. As HTLV-1/-2, which, in addition to dendritic cells, infect activated CD4þ and CD8þ T cells, respectively in vivo, we have shown that HTLV-3 surface envelope glycoprotein (gp46 or SU) binds to both activated CD4þ and CD8þ T, but also to naïve CD4þ T cells (Jones et al, 2009). The latter do not bind HTLV-1 or HTLV-2 SU and do not express detectable levels of heparan sulfate proteoglycans (HSPGs), neuropilin-1 (NRP-1) and Glucose transporter 1 (GLUT-1).…”
Section: Htlv-3/-4 Cell Entrymentioning
confidence: 97%
“…An earlier study reported that overexpression of GLUT1 in a cell line (COS-7) increased cell-cell transmission, but did not increase the level of binding of the SU-Fc protein [ 57 ]. Similarly, more recent studies using clones of the U87 cell line that express different levels of GLUT1 have observed that the level of cell surface GLUT1 correlates with the titer of HTLV-1 Env pseudotyped viruses, but not with SU-Fc binding [ 58 ]. All these findings suggested that molecules other than GLUT1 are also involved in HTLV-1 entry, especially at the binding step.…”
Section: Not One But Three Receptor Molecules: Glut1 Hspg and Nrp-1mentioning
confidence: 99%